Stress-induced anhedonia is associated with hypertrophy of medium spiny neurons of the nucleus accumbens - João, Bessa (2013)
There is accumulating evidence that the nucleus accumbens (NAc) has an important role in the pathophysiology of depression. As the NAc is a key component in the neural circuitry of reward, it has been hypothesized that anhedonia, a core symptom of depression, might be related to dysfunction of this brain region. Neuronal morphology and expression of plasticity-related molecules were examined in the NAc of rats displaying anhedonic behavior (measured in the sucrose-consumption test) in response to chronic mild stress. To demonstrate the relevance of our measurements to depression, we tested whether the observed changes were sensitive to reversal with antidepressants (imipramine and fluoxetine). Data show that animals displaying anhedonic behavior display an hypertrophy of medium spiny neurons in the NAc and, in parallel, have increased expression of the genes encoding for brain-derived neurotrophic factor, neural cell adhesion molecule and synaptic protein synapsin 1. Importantly, the reversal of stress-induced anhedonia by antidepressants is linked to a restoration of gene-expression patterns and dendritic morphology in the NAc. Using an animal model of depression, we show that stress induces anhedonic behavior that is associated with specific changes in the neuronal morphology and in the gene-expression profile of the NAc that are effectively reversed after treatment with antidepressants.